ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BENTUK ALJABAR MENGGUNAKAN PROSEDUR NEWMAN - Angelia Augifty Evan Karouw; Nicky K. Tumalun; Jorry F. Monoarfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2023)
The mistakes made by students are not known for sure what the form of the error is. Therefore, these errors need to be identified through the results of students' answers in solving algebraic story questions and reviewing whether students understand the meaning of the questions, whether students can develop plans for solving them, whether students can carry out the completion plans and whether students re-examine the final answers to determine conclusions. In this study, errors were obtained based on Newman's completion steps, the most frequent mistakes made by students were process skills errors with a percentage of 38.77%, followed by writing errors with a percentage of 36.73%, then transformation errors with a percentage of 22.44%, then understanding error with a percentage of 12.24% and the last reading error with a percentage of 2.04%.Keywords : Newman, Error Analysis, Algebraic Forms of Story Problems